Biocontrol of fungal phytopathogens by Bacillus pumilus - Dobrzyński, Jakub; Jakubowska, Zuzanna; Kulkova, Iryna; Kowalczyk, Paweł; Kramkowski, Karol (Frontiers in Microbiology, 2023)
Plant growth-promoting bacteria are one of the most interesting methods of controlling fungal phytopathogens. These bacteria can participate in biocontrol via a variety of mechanisms including lipopeptide production, hydrolytic enzymes (e.g. chitinase, cellulases, glucanase) production, microbial volatile organic compounds (mVOCs) production, and induced systemic resistance (ISR) triggering. Among the bacterial genera most frequently studied in this aspect are Bacillus spp. including Bacillus pumilus. Due to the range of biocontrol traits, B. pumilus is one of the most interesting members of Bacillus spp. that can be used in the biocontrol of fungal phytopathogens. So far, a number of B. pumilus strains that exhibit biocontrol properties against fungal phytopathogens have been described, e.g. B. pumilus HR10, PTB180, B. pumilus SS-10.7, B. pumilus MCB-7, B. pumilus INR7, B. pumilus SE52, SE34, SE49, B. pumilus RST25, B. pumilus JK-SX001, and B. pumilus KUDC1732. B. pumilus strains are capable of suppressing phytopathogens such as Arthrobotrys conoides, Fusarium solani, Fusarium oxysporum, Sclerotinia sclerotiorum, Rhizoctonia solani, and Fagopyrum esculentum. Importantly, B. pumilus can promote plant growth regardless of whether it alters the native microbiota or not. However, in order to increase its efficacy, research is still needed to clarify the relationship between the native microbiota and B. pumilus. Despite that, it can already be concluded that B. pumilus strains are good candidates to be environmentally friendly and commercially effective biocontrol agents.